Case Report: Novel ADAMTSL2 compound heterozygous mutations in geleophysic dysplasia with bilateral glaucoma and keratoconus-like corneal ectasia - Lee, Chung-Lin; Chuang, Chih-Kuang; Chiu, Huei-Ching; Chang, Ya-Hui; Tu, Yuan-Rong; Lo, Yun-Ting; Wu, Jun-Yi; Lin, Hsiang-Yu; Lin, Shuan-Pei (Frontiers in Genetics, 2026)
Geleophysic dysplasia represents an exceedingly uncommon autosomal recessive skeletal disorder marked by profound growth restriction, contractures affecting multiple joints, and cardiac valve abnormalities. The molecular foundation involves ADAMTSL2 gene mutations disrupting extracellular matrix architecture. We document a 29-year-old Taiwanese woman followed longitudinally for 25 years, presenting with severe short stature measuring 141.2 cm, widespread joint contractures, thoracolumbar scoliosis, and distinctive gait abnormalities. Whole-exome sequencing identified compound heterozygous ADAMTSL2 mutations: c.286C>T resulting in p. Arg96Trp and c.454_459del causing p. Cys152_Thr153del deletion. The clinical course revealed musculoskeletal deterioration alongside mild mitral valve involvement and os odontoideum. Bilateral glaucoma, consistent with previously reported ocular manifestations in geleophysic dysplasia, was diagnosed at age 26. Notably, recent ophthalmologic evaluation revealed keratoconus-like corneal ectasia with paradoxically increased central corneal thickness measuring 690–693 μm bilaterally, substantially exceeding normal values of 520–560 μm. This paradoxical corneal thickening, contrasting with the stromal thinning characteristic of classical keratoconus, represents a novel ADAMTSL2-related corneal phenotype. The patient maintained normal intellectual capacity despite physical limitations, contrasting with published early mortality rates approaching 33%. This extended clinical documentation establishes keratoconus-like corneal ectasia with paradoxical corneal thickening as a novel ophthalmologic manifestation in geleophysic dysplasia, while adding to prior reports of glaucoma in this condition. These findings emphasize the necessity for comprehensive ophthalmologic monitoring in ADAMTSL2-related disorders and supporting multidisciplinary management strategies.